Always Italy - Mayes, Frances (National Geographic, 2020)
This lush guide, featuring more than 350 glorious photographs from National Geographic, showcases the best Italy has to offer from the perspective of two women who have spent their lives reveling in its unique joys. In these illuminating pages, Frances Mayes, the author of Under the Tuscan Sun and many other bestsellers, and New York Times travel writer Ondine Cohane reveal an Italy that only the locals know, filled with top destinations and unforgettable travel experiences in every region. From the colorful coastline of Cinque Terre and the quiet ports of the Aeolian Islands to the Renaissance architecture of Florence and the best pizza in Rome, every section features insider secrets and off-the-beaten-path recommendations (for example, a little restaurant in Piedmont known for its tajarin, a pasta that is the perfect bed for the region's celebrated truffles). Here are the best places to stay, eat, and tour, paired with the rich history of each city, hillside town, and unique terrain. Along the way, you'll make stops at the country's hidden gems--art galleries, local restaurants, little-known hiking trails, spas, and premier spots for R&R. Inspiring and utterly unique, this vivid treasury is a must-have for anyone who wants to experience the best of Italy.